ANALYSIS OF COMPENSATION AND WORKLOAD FOR EMPLOYEE JOB SATISFACTION AT PT AKL - Redy Adhi Saputra (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This study aims to determine and analyze the effect of compensation and workload on employee job satisfaction at PT Aneka Kimia Lestari. The study uses a quantitative approach with a survey method. The population in this study were all 85 employees of PT Aneka Kimia Lestari, with a sampling technique using saturated sampling so that the entire population was used as a research sample. Data were obtained through distributing questionnaires using Google Form with a four-point Likert scale. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination using the IBM SPSS Statistics application. The results showed that compensation had a positive and significant effect on employee job satisfaction with a significance value of 0.000 <0.05 and a t-value of 11.426. Meanwhile, workload had a negative but insignificant effect on job satisfaction with a significance value of 0.544 >0.05 and a t-value of -0.612. Simultaneously, compensation and workload have a significant effect on employee job satisfaction with a calculated F value of 134.893 and a significance of 0.000 < 0.05. The Adjusted R Square value of 0.867 indicates that compensation and workload are able to explain employee job satisfaction by 86.7%, while the rest is influenced by other variables outside the study. The implications of this study indicate that companies need to maintain a fair compensation system that is in accordance with employee contributions and pay attention to the distribution of workloads so that it remains proportional in order to increase employee job satisfaction and support the achievement of company goals.